(untitled) (CIPEEX, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that affects the organization of thoughts, feelings, and emotions. Its characteristics include difficulties with communication, socialization, and restricted, repetitive behaviors. In this context, students from the Nursing program at the Evangelical University of Goiás – Ceres Campus visited the Richarlison Alves Caetano Rehabilitation Center in Uruana-GO to learn about and report on the operation of the Integrar Project, which aims to help children with autism develop essential skills for daily life and social inclusion. The methodology used was a structured interview with the pedagogue responsible for the institution. In the analysis of the collected data, the professional explained that the physical structure of the project is suitable for meeting the patients’ needs, providing a calm and welcoming environment. The main objective of the project is to improve the behavior and social interaction of patients, both in family and school settings. Positive experiences highlighted include the acceptance of most parents and the patients themselves of the treatment, resulting in significant progress. Regarding its operation, consultations occur three times a week, with 40-minute sessions, in addition to a weekly group session to promote social interaction and assess the children’s progress. The project serves 60 patients and conducts more than 300 weekly appointments, accommodating more than one child per session in some cases. The team consists of four interns, one trained professional, a speech therapist, and a therapeutic assistant. Among the main challenges the project faces, the resistance of some parents, who abandon treatment halfway, was mentioned, which hinders the children’s development. Furthermore, the institution faces a long waiting list, especially for children with ASD, due to the indefinite duration of the treatment. Another challenge to overcome is the lack of resources and qualified professionals, as well as legal and community support. The toys used are donated, and despite receiving medical, psychological, and nursing support, as well as occupational therapy, the lack of public financial support limits the scope of activities. The visit revealed the importance of the Integrar Project in developing children’s skills, promoting their future independence, where community and family integration is fundamental. Although the institution faces significant challenges, investing in resources, infrastructure, and community awareness is essential to promote inclusion and improve the quality of life for people with ASD.